Competing in the Digital Age : Policy Implications for the Russian Federation - World Bank Group (World Bank, Washington, DC, 2018)
This report provides an overview of the role of emerging technologies in digital transformation and the global best practices in policy responses to the disruptions they cause across a broad spectrum of economic activity. It analyzes the successes and challenges of digital transformationin Russia and attempts to develop key recommendations to help policy makers accelerate the pace of digital transformation across the main sectors of the Russian economy. In its current version, the report starts with discussing the results of the Russia DECA and offers an analysis of international best practice in formulating policy approaches to stimulate digital adoption while easing the disruption caused by the rapid emergence of new technologies. The objective is to help policy makers think through ways to harness the opportunities created by emerging technologies to enable Russia to accelerate the pace of digital transformation. The report then discusses the emergence of digital platforms as key enablers of digital transformation and proceeds to explore sectoral dynamics in the key digital transformation areas outlined in the Russia Digital Economy Program, including digital government, digital business, as well as digital innovation and skills building. Sector-oriented chapters follow a similar structure by analyzing international best practice in the transformation of a sector, offering an assessment of the current state of transformation of that sector in Russia and concluding with proposing a set of recommendations that may help accelerate the digital transformation of the sector in light of international best practice and the local experience. Due to the rapid pace of technological change and space limitations, this report does not pretend to offer in-depth analysis of Russian digital transformation at the sectoral level but is rather an attempt to analyze global best practice to inform Russian policy making and an invitation to the policy-maker and expert community to continue the digital co-creation experience started two years ago in the hope that it is an effective way to share the just-in-time global expertise of the World Bank whenever and wherever it is needed most in order to help accelerate Russia’s digital transformation process.